Geometrical predictors of small virtual neoLVOT size in functional mitral regurgitation. (25th November 2020) - Reid, A; Anastasius, M; Ben Zekry, S; Turaga, M; Webb, J; Boone, R; Moss, R; Cheung, A; Ye, J; Leipsic, J; Blanke, P
Abstract: Background: LVOT obstruction is a potentially lethal complication of transcatheter mitral valve replacement (TMVR). An anticipated neoLVOT area of <2cm 2 is presumed to imply prohibitive risk. Measurement of the anticipated neoLVOT can be time consuming and requires specialist software to facilitate virtual valve implantation. Purpose: To determine simple geometrical predictors of prohibitive neoLVOT size. Methods: 165 consecutive, non-calcific FMR patients referred to a transcatheter heart valve program were analysed. Segmentation of the mitral annulus and left heart geometry was performed using CT. Suitability for a default D-shaped TMVR was determined by proprietary annular inclusion criteria. Systolic neoLVOT area was determined via virtual valve implantation of the default TMVR. Results: Sufficient image data for annular and neoLVOT suitability assessment was available in 152 patients. 105 patients (69%) were suitable for TMVR based on annular measurements. Of these, neoLVOT area was >2cm 2 in 88 (84%). Overall, compared to patients not suitable for TMVR (n=64), those suitable had larger ventricles with lower LVEF, and larger annuli (table 1). Using binomial logistic regression involving the variables within table 1, LVESD was the sole statistically significant variable to predict neoLVOT area of <2cm 2 (p=0.02). LVESD <48mm had 82% sensitivity and 94% specificity for the presence of prohibitive neoLVOT (figure 1). Conclusion: Smaller LVESD is a strong predictor of small neoLVOT, and hence LVOT obstruction post default D-shaped TMVR implantation. This simple measure may therefore be used to streamline patient selection for advanced pre-procedural imaging analysis. Funding Acknowledgement: Type of funding source: None